2018
DOI: 10.1016/j.ijmedinf.2018.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Health information management practices in informal caregiving: An artifacts analysis and implications for IT design

Abstract: Introduction: Unpaid informal caregivers of adult care recipients, including persons with dementia, experience multiple unmet information needs and information management challenges. Objectives: To understand the current personal health information management (PHIM) practices in informal caregiving for adults with and without dementia. Methods: Semi-structured interviews were performed with ten informal caregivers-half of whom were caring for persons with dementia-and four formal caregivers at an adult day ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…Participants still felt that there were time constraints and reported technological issues as barriers to effectively using the PHR-ADRD system. These findings align with a recent study that identified several ways in which another similar internet-based medical management tool was perceived as difficult to use: caregivers were reluctant to add another management tool to their already busy day-to-day activities, found the system itself difficult to use in terms of cognitive workload, and reported the system’s tools to be of limited dynamic functioning [ 57 ]. Although this study’s participants did not feel particularly lost using the PHR site, systems designed for ADRD caregivers need to pay extra attention to user interface design to equitably reduce cognitive and time burdens for users from all technological backgrounds [ 58 ].…”
Section: Discussionsupporting
confidence: 87%
“…Participants still felt that there were time constraints and reported technological issues as barriers to effectively using the PHR-ADRD system. These findings align with a recent study that identified several ways in which another similar internet-based medical management tool was perceived as difficult to use: caregivers were reluctant to add another management tool to their already busy day-to-day activities, found the system itself difficult to use in terms of cognitive workload, and reported the system’s tools to be of limited dynamic functioning [ 57 ]. Although this study’s participants did not feel particularly lost using the PHR site, systems designed for ADRD caregivers need to pay extra attention to user interface design to equitably reduce cognitive and time burdens for users from all technological backgrounds [ 58 ].…”
Section: Discussionsupporting
confidence: 87%
“…Technology solutions are not optimized to specific informal caregiver needs as it could be hard to recognize themselves in the information provided through ICT [ 26 ]. The content delivered via ICT solutions is often static and not specific to caregiving needs [ 34 , 41 ]. The literature reported that the experience of seeking information about caregiving situations using ICT solutions appeared to be a chaotic and confusing process, as informal caregivers need to access multiple information routes to get the information they need [ 34 , 37 , 38 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…The literature reported that the experience of seeking information about caregiving situations using ICT solutions appeared to be a chaotic and confusing process, as informal caregivers need to access multiple information routes to get the information they need [ 34 , 37 , 38 , 55 ]. In many studies, informal caregivers reported difficulties in finding specific and up-to-date information related to their caregiving situation which adapts to changing needs over time [ 41 , 48 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [44] an algorithm, called Sequential Risk Sampling (SeqRTS), was developed to distribute notifications in a uniform way across all risk times. With reference to homecare, the work in [45] addressed the Personal Health Information Management (PHIM) practices, by sharing the information with the medical staff, in informal care-giving for patients with/without dementia.…”
Section: Applications Of Medical Guismentioning
confidence: 99%